A market-based and synthesised approach to controlling price gouging. (5th January 2011) - Chen, Andy C.M.
This paper compares and evaluates the various controlling mechanisms to price gouging after natural or man-made disasters. Events in Taiwan illustrate how contract principles, anti-gouging laws, and competition laws individually affect post-disaster price hikes. Their advantages and limits are discussed. The study purpose argues in favour of a market-based approach under which competition law is central to government-enforcement efforts. This approach allows the inclusion of the market's self-adjusting force into the review process, which is frequently neglected by the other controlling mechanisms. Furthermore, it also sheds light into how other controlling mechanisms should be implemented. Overall, the market-based approach suggests that both the courts and the regulatory agencies benefit from accommodating the fundamental principles of competition law to maintain the reversibility and flexibility in their decisions.